Outcome of using olive oils for MWCNT functionalization and the influence of –OH modified MWCNTs on PA and PBT nano-composites. (2020) - Chopra, Swamini; Ramanadham, Vyshnavi; Vullengala, Sai Prasanna; Tiwari, Shruti; Lad, Komal; Deshmukh, Kavita A.; Peshwe, D.R.
Abstract: The effective utilization of carbon nanotubes (CNTs) in polymer matrix depends strongly on their ability to homogeneously disperse throughout the matrix without destroying the structural integrity. The tendency of the CNTs to agglomerate within polymer matrix increases due to the van der Waals force of attraction between individual nanotubes. Thus, the uniform dispersion of the CNTs can be achieved by modifying their surface with the attachment of different functional groups, most commonly by refluxing them in acids in a process known as Functionalization. Despite achieving the improvement in the dispersion quality of CNTs after functionalization in acids, it was noted that the nanotubes got damaged due to the strong interaction of acids. The acid attack on the structure of CNTs causes unwanted defects onto the CNT surface. Thus, alternate routes of functionalizing the CNTs are in dire need. Thus, an effort has been made to explore the use different functionalization mediums that are not as harsh as acids but still are able to functionalize the CNTs to an acceptable extent. Keeping this in view, the present work focuses on functionalizing the MWCNTs using two types of olive oils and comparing their effectiveness with that of H2 O2 acid as an medium for –OH functionalization of MWCNTs. The functionalized MWCNTs are further reinforced into PA and PBT polymer matrices for property evaluation in comparison with the non-functionalized MWCNT reinforced nano-composites.